Postangioplasty restenosis: a practical model in the porcine carotid artery - Caramori,P.R.A. (1997)
Transluminal coronary angioplasty is a routine therapeutic intervention in coronary heart disease. Despite the high rate of primary success, restenosis continues to be its major limitation. Porcine models have been considered to be the most adequate experimental models for studying restenosis. One limitation of porcine models is the need for radiological guidance and the expenses involved. The objective of the present study was to adapt an experimental model of angioplasty in the porcine carotid artery that does not require radiological equipment. Eight animals were used to develop the technique of balloon injury to the common carotid artery by dissection without radiological guidance. This technique was then employed in six other animals. Under anesthesia, the left common carotid artery was dissected and incised at the carotid sinus for insertion of an over-the-wire angioplasty balloon towards the aorta. Overstretch injury of the carotid artery was performed under direct visualization. After 30 days, the arteries were excised and pressure-fixated. Uninjured carotid arteries from 3 additional animals were used as controls. A decreased luminal area associated with intimal hyperplasia and medial reaction was observed in all injured arteries. Immunohistochemistry identified the intimal hyperplastic cells as smooth muscle cells. Computerized morphometry of the ballooned segments revealed the following mean areas: lumen 2.12 mm2 (± 1.09), intima 0.22 mm2 (± 0.08), media 3.47 mm2 (± 0.67), and adventitia 1.11 mm2 (± 0.34). Our experimental model of porcine carotid angioplasty without radiological guidance induced a vascular wall reaction and permitted the quantification of this response. This porcine model may facilitate the study of vascular injury and its response to pharmacological interventions